2020
DOI: 10.1039/c9ra10347c
|View full text |Cite
|
Sign up to set email alerts
|

Xanthohumol from Humulus lupulus L. potentiates the killing of Mycobacterium tuberculosis and mitigates liver toxicity by the combination of isoniazid in mouse tuberculosis models

Abstract: Anti-tuberculosis drug induced hepatotoxicity is the main problem in tuberculosis patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…The authors found no references to studies that investigated the antimicrobial effect of hops effect against Mycoacterium bovis. It was interesting to note from Table 4 that although there are a number of studies which investigated the antimicrobial effect of hops against mycobacteria [11][12][13]25] and as additives in ruminant feedstuffs [31] or for their potential use in methane reduction [6], there were no studies which investigated the use of hops against Mycoacterium bovis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors found no references to studies that investigated the antimicrobial effect of hops effect against Mycoacterium bovis. It was interesting to note from Table 4 that although there are a number of studies which investigated the antimicrobial effect of hops against mycobacteria [11][12][13]25] and as additives in ruminant feedstuffs [31] or for their potential use in methane reduction [6], there were no studies which investigated the use of hops against Mycoacterium bovis.…”
Section: Discussionmentioning
confidence: 99%
“…The antimicrobial activity of hops has previously been linked to the hop alpha acid humulone, beta acid lupulone and polyphenol xanthohumol [22,25]. Gerhauser (2005) demonstrated the antibacterial activity of xanthohumol against the Gram-positive microorganisms Staphylococcus aureus and Streptococcus mutans along with antiviral and antiparasitic activity [36].…”
Section: Type Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…85 XN and lupulone showed strong antibacterial properties among the studied compounds. 86 Lou et al 87 investigated the combined effect of XN with isoniazid against mice infected with Mycobacterium tuberculosis. 87 In another study, the antimicrobial activities of hops were investigated against Streptococcus iniae and Vibrio vulnificus.…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…86 Lou et al 87 investigated the combined effect of XN with isoniazid against mice infected with Mycobacterium tuberculosis. 87 In another study, the antimicrobial activities of hops were investigated against Streptococcus iniae and Vibrio vulnificus. It has been reported that XN shows the strongest antibacterial property against Streptococcus.…”
Section: Antimicrobial Activitymentioning
confidence: 99%